.7(x+60)+.9x=106

Simple and best practice solution for .7(x+60)+.9x=106 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .7(x+60)+.9x=106 equation:


Simplifying
0.7(x + 60) + 0.9x = 106

Reorder the terms:
0.7(60 + x) + 0.9x = 106
(60 * 0.7 + x * 0.7) + 0.9x = 106
(42 + 0.7x) + 0.9x = 106

Combine like terms: 0.7x + 0.9x = 1.6x
42 + 1.6x = 106

Solving
42 + 1.6x = 106

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + -42 + 1.6x = 106 + -42

Combine like terms: 42 + -42 = 0
0 + 1.6x = 106 + -42
1.6x = 106 + -42

Combine like terms: 106 + -42 = 64
1.6x = 64

Divide each side by '1.6'.
x = 40

Simplifying
x = 40

See similar equations:

| 7x-4+5x=20 | | 5.9t-9.5=-12.5+4.9t | | 5m+7-2m-1= | | 11S^2+S-10=0 | | 17=m+3 | | 4x-2x+5=-7 | | 6y-5y-3=8 | | 25=m+4 | | 8k^2=688 | | 6s=-36 | | x+172+32+x=180 | | 7+z=12 | | -3(x-1)=4(3-2x)+7 | | 6x-7-3x= | | h+31=-22 | | 4x+6y=1080 | | x^2+9=59 | | 9(t+2)=6(t-2) | | 0.9=-8c+0.5+9c+0.2 | | 28=m-5 | | h-2=4 | | -5(6y-6)-y=-2(y-3) | | ln(x-3)-2=8 | | 2+(-5)=x | | 2(x+4)-16=20 | | 1.5y+6= | | 2x+9=x^2 | | m+29=-52 | | x-48=-47 | | 7x-3+11x+3=162 | | 3kx^2-2kx+1=0 | | 3.6=r-2.3 |

Equations solver categories